Pendampingan Pembuatan Bahan Ajar Berbasis Multimedia Menggunakan Macromedia Flash Bagi Para Guru SD IT Salsabila Al Muthi’in, Yogyakarta - Dwi Nugraheny; Hero Wintolo; Anggraini Kusumaningrum; . Sudaryanto (Institut Teknologi Dirgantara Adisutjipto, 2018)
Teachers are a very noble profession, because one of the teachers task is to help in the intellectual life of the nation. As teachers in their daily life to educate the nation, requires the support of equipment that can be used in the teaching and learning process in the field that he has. Supporting equipment required can be hardware and software that can be utilized to compile teaching materials that are interesting for the students, one of them is multimedia-based teaching materials. As a lecturer in the field of informatics, we are motivated to assist teachers especially teachers in SD IT Salsabila Al Muthi'in, Yogyakarta by doing the process of mentoring in the making of multimedia-based teaching materials using Macromedia Flash.